Berkeley: The role of God in the theory of vision - Alberto Luis López (Tópicos, 2015)
Berkeley develops his theory of vision in the early work An Essay Towards a New Theory of Vision, which has generally been read only attending its scientific or perceptual aspects. In this pa- per I propose a different reading of the Essay. My reading wants to show that this work not only attend scientific aspects but, on the contrary, anticipates the immaterialism of later works. It does this because God plays an important role in it, which is due, among other things, that theory of vision is developed according to God, since of Him depends both sight and visible objects and visual language argument.